(untitled) (Bangladesh Journal of Zoology, 2026)
The nesting and breeding ecology of the Great Egret was studied in north and northeastern Bangladesh from 2017 to 2023. Out of 199 colony sites, 111 (55.78 %) were actively breeding, 38 (19.10 %) served as night roosts, and 50 (25.12 %) were abandoned. The active breeding colony sites covered a total of 92.12 hectares, with the majority situated on private land (89.92 ha) and only a small portion on government land (2.20 ha). The highest number of active breeding colonies occurred in Naogaon (n = 22), followed by Sylhet (n = 14) and Habiganj (n = 9), while Bogura, Natore, Rajshahi, and Jamalpur each had only one (n = 1). Of the 5,755 nests counted, the largest proportion was in Naogaon (20.94%), followed by Netrokona (17.74%) and Sylhet (7.91%), with the lowest in Bogura (0.21%). Active breeding colonies were predominantly in paddy field-dominated habitats (71.17%, n = 79), with smaller proportions in wetlands (9.91%, n = 11), mixed agriculture (9.01%, n = 10), tea gardens (4.50%, n = 5), orchards (2.70%, n = 3), and homestead areas (2.70%, n = 3). Breeding occurred from April to September, with colony sizes ranging from 2 to 302 nests. Nesting occurred on 1,258 plants across 34 species, with a preference for Bambusa spp. (40.31%), followed by Mangifera indica (15.57%), Swietenia mahagoni (8.98%), and Tamarindus indica (8.06%); the average nesting height was 10.39 ± 2.41 m (range 5.2-16.41 m, n = 1,258). Clutches averaged 2-4 eggs (mean 2.78 ± 0.71, n = 18), laid over 4-9 days. The incubation period lasted 23–28 days, chicks fledged after 40-55 days, and overall breeding success was 74%. Bangladesh J. Zool. 53(3): 373-388, 2025